Joint-level proprioceptive deficits and postural instability in Fibromyalgia: a biomechanical assessment using digital inclinometry and dynamic posturography - Kandakurti, Praveen Kumar; Reddy, Ravi Shankar; Alnakhli, Hani Hassan; Alkhamis, Batool A.; Koura, Ghada M.; ALMohiza, Mohammad A.; Alyazedi, Faisal M.; Mukherjee, Debjani; Rao, Vikram Sreenivasa (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveFibromyalgia syndrome (FMS) is characterized by chronic musculoskeletal pain, fatigue, and sensory disturbances, often leading to impaired proprioception and postural control. This study aimed to examine joint reposition sense (JRS) at the hip, knee, and ankle, alongside limits of stability (LOS), in elderly individuals with FMS using digital inclinometers and computerized posturography.MethodsA total of 108 participants (54 with FMS, 54 age-matched healthy controls) were assessed. JRS was assessed at standardized joint angles of the hip (60° flexion), knee (45° flexion), and ankle (15° plantarflexion) using calibrated digital inclinometers, while LOS parameters—reaction time, maximum excursion, and directional control—were recorded with dynamic posturography.ResultsParticipants with FMS showed significantly higher joint position errors at the hip (mean difference = 2.53°), knee (2.51°), and ankle (2.24°) (p < 0.001, Cohen’s d > 1.8). LOS parameters were also impaired in the FMS group, with slower reaction time (Δ = 0.97 s), reduced maximum excursion (Δ = −3.44%), and lower directional control (Δ = −22.64%) (all p < 0.001). JRS errors negatively correlated with LOS metrics, particularly at the hip and knee. Regression analysis confirmed JRS as a significant predictor of postural control.ConclusionLower limb proprioceptive deficits significantly impact postural stability in individuals with FMS. Targeted proprioceptive training, especially at the hip and knee, may improve functional balance and reduce fall risk in this population.